Political Repressions in the Mongol Empire, Golden Horde and Other Turkic-Mongol States, and their Justifications (13th–16th cc.) - R.Yu. Pochekaev (Золотоордынское обозрение)
In this article the author analyses the cases of political repressions in the Mongol Empire, Golden Horde and other Turkic-Mongol states of the 13th–16th centuries. Author investigates different types of repressions: against rivals during the struggle for the throne, officials who incurred the anger of monarchs, rebellious cities and their citizens. So, the political rivals often justified their right to the throne referring to the Great Yasa of Chinggis Khan, and hence, the punishment of the vanquished rivals usually was based as well on the Chinggis Khan’s principles of the “Law and Order”: ambiguity of these principles (since the Great Yasa, as it seems, was not a written code of laws but only a system of rules and principles proclaimed by Chinggis Khan or his successors, who attributed them to him) allowed the winners to avenge their rivals following the formal legal norms. Thus, the charge of violation of the Great Yasa was a universal one allowing to solve the problem of of getting rid of a dangerous rival. The punishment of disgraced officials was justified by other arguments that differed from charges of rebellion of the Chinggisid family members. But Chinggisid rulers also used some “standard” accusations such as treason, support of usurpers, bribery. Since in most cases such acts also contradicted to the principles of the Great Yasa (as they were interpreted by the Chinggisids), the formula “put to yasa” was frequently used in verdicts on such cases. At last, we can also include the destruction of the resisting and insurgent cities in terms of political repressions. Reprisals against foreign cities that resisted the Mongol conquerors, was an integral part of the military strategy of terror facilitating the voluntary surrender of the following cities. In this case, the Chinggisids did not need any legal basis for the slaughter and destruction. However, in case of the rebellion of their own cities against the legitimate monarch, the latter, dealing with them accordingly, always represented his actions as the restoration of law and order. So, despite the fact that in most of such cases repressions were result of personal decision of the monarch, or revenge, or coup d’etat, etc., we can make sure that almost all of such repressions (with rare exceptions) were presented only as a punishment of criminals, traitors, bribe-takers and so on.